The respiratory mechanics of the yacare caiman (Caiman yacare) - Reichert, Michelle N.; Oliveira, Paulo R. C. de; Souza, George M. P. R.; Moranza, Henriette G. [UNESP]; Restan, Wilmer A. Z. [UNESP]; Abe, Augusto S. [UNESP]; Klein, Wilfried; Milsom, William K. (Company Biologists Ltd, 2019)
The structure and function of crocodilian lungs are unique compared with those of other reptiles. We examined the extent to which this and the semi-aquatic lifestyle of crocodilians affect their respiratory mechanics. We measured changes in intratracheal pressure in adult and juvenile caiman (Caiman yacare) during static and dynamic lung volume changes. The respiratory mechanics of juvenile caiman were additionally measured while the animals were floating in water and submerged at 30, 60 and 90 deg to the water's surface. The static compliance of the juvenile pulmonary system (2.89 +/- 0.22 ml cmH(2)O(-1) 100 g(-1)) was greater than that of adults (1.2 +/- 0.41 ml cmH(2)O(-1) 100 g(-1)), suggesting that the system stiffens as the body wall becomes more muscular and keratinized in adults. For both age groups, the lungs were much more compliant than the body wall, offering little resistance to air flow (15.35 and 4.25 ml cmH(2)O(-1) 100 g(-1) for lungs, versus 3.39 and 1.67 ml cmH(2)O(-1) 100 g(-1) for body wall, in juveniles and adults, respectively). Whole-system dynamic mechanics decreased with increasing ventilation frequency (f(R)), but was unaffected by changes in tidal volume (V-T). The vast majority of the work of breathing was required to overcome elastic forces; however, work to overcome resistive forces increased proportionally with f(R). Work of breathing was higher in juvenile caiman submerged in water at 90 deg because of an increase in work to overcome both elastic and flow resistive forces. The lowest power of breathing was found to occur at high f(R) and low V-T for any given minute ventilation ((V) over dot(E)) in caiman of all ages.
Keywords: Crocodilia; Static compliance; Dynamic compliance; Elastic forces; Resistive forces; Work of breathing